Physictherapy Center - RAIE, HAYA (My University, 2022)
The main concept of the centre is to provide medical treatment services, in addition to the fact that it is used as a resort (to stay in), it consists of: examination, detection and providing the suitable treatment for them, in addition to the post-treatment rehabilitation phase, it also provides health services including sauna, massages, gums, etc... Also it provides bedrooms for those who want to stay in for relaxing. The main reason for choosing the project is to spread awareness and culture of physical therapy away from chemical interventions, which negatively affect the body in the long turn. It was also proposed to design this project in the Dead Sea area, in order to exploit the natural resources in Palestine of minerals and salts useful for the human body